Modal Analysis of Gearbox based on the Method of ERA - Zhang Lin; Ma Weijin; Huang Bincheng; Ge Yumin; Wen Fang (Jixie chuandong)
Based on the method of ERA,a system of modal analysis is built,the model of HW25505 TCL gearbox is set up under the Coinv DASP MAS modal analysis module.The relating modal datum are obtained by hammering test of single-input multi- output analysis method,then the state-space equation is established after the analysis of modal datum.The various modal parameters of the gearbox are obtained by order selection and fitting of the datum which extracted through the method of ERA modal parameter identification,and by using modal correlation matrix,the modal test and verification are carried out.Through the comparison with calculating modal,the validity and reliability are proved.The theoretical basis for the improvement of the gear box structure characteristics and the fault diagnosis of gearbox is provided.